Prognostic value of liver stiffness in HIV/HCV-Coinfected patients with decompensated cirrhosis - Leire Pérez-Latorre; Matilde Sánchez-Conde; Pilar Miralles; Juan Carlos López; Francisco Parras; Francisco Tejerina; Teresa Aldámiz-Echevarría; Ana Carrero; Cristina Díez; Margarita Ramírez; Isabel Gutiérrez; José María Bellón; et al. (BMC Infectious Diseases, 2018)
Abstract Background Little is known about the utility of transient elastography (TE) for assessing the prognosis of patients with decompensated cirrhosis (DC). Methods We analyzed HIV/HCV-coinfected patients with DC who underwent TE as part of their routine follow-up between 2006 and 2015. We also calculated the liver stiffness spleen diameter-to-platelet score (LSPS), FIB-4 index, albumin, MELD score, and Child-Pugh score. The primary outcome was death. Results The study population comprised 65 patients. After a median follow-up of 32 months after the first TE, 17 patients had received anti-HCV therapy and 31 patients had died. The highest area under the receiver operating characteristic curve (AUROC) value for prediction of death was observed with albumin (0.695), followed by Child-Pugh score (0.648), both with P values < .05. Lower AUROC values were observed with MELD score (0.633), TE (0.618), LSPS score (0.595), and FIB-4 (0.569), all with P values > .05. In the univariate Cox regression analysis, albumin, FIB-4, Child-Pugh score, and MELD score, but not TE, were associated with death. In the multivariate analysis, albumin and Child-Pugh score were the only baseline variables associated with death. Conclusions Our results suggest that TE is not useful for assessing the prognosis of HIV-infected patients with decompensated HCV-related cirrhosis. Albumin concentration and Child-Pugh scores were the most consistent predictors of death in this population group.